Anomalous Origin of the Right Coronary Artery From the Mid-Portion of the Left Anterior Descending Artery - Khan, Rozi (Cureus, 2020)
Coronary artery anomalies (CAAs) are rare findings and usually diagnosed incidentally on coronary angiograms for other cardiac conditions in most cases. However, coronary anomalies are being increasingly reported with the invention of more advanced cardiac imaging techniques. The CT of the heart structure is the best modality to diagnose and track the exact course of the anomalous artery and to guide in proper management. Anomalous course of the right coronary artery (RCA) between the aorta and pulmonary artery may cause compression and require surgical intervention given the risk of myocardial ischemia and sudden death. In this report, we discuss the case of a 69-year-old female with no prior cardiac comorbidities. The patient had been referred from the primary care office for cardiac clearance to undergo bilateral knee replacement surgery. On further inquiry, she reported a history of murmur and stated that she had been having dyspnea on exertion over the last six months. Precordial examination revealed a 2/6 ejection systolic murmur. Transthoracic echocardiogram showed severe aortic stenosis. For further evaluation, she underwent a coronary angiogram, which showed right dominant coronary system, normal left main with no stenosis, a large septal branch that had anomalously originated from left main and coursing all the way to the apex, and the RCA originating from the mid-portion of the left descending artery. The cardiac CT scan showed the exact course of the anomalous origin of the RCA from the mid-left anterior descending artery (LAD). The RCA coursed anteriorly to the main pulmonary artery/right ventricular outflow tract to reach the right atrioventricular groove. The patient underwent transcatheter aortic valve replacement (TAVR) and was discharged in stable condition.